1997
DOI: 10.1007/bf02917472
|View full text |Cite
|
Sign up to set email alerts
|

Trace element status of hemodialyzed patients

Abstract: The trace elements Ba, Bi, Cd, Co, Cs, Cu, Hg, La, Mn, Mo, Pb, Rb, Sb, Sn, Sr, Tl, and Zn were determined by inductively coupled plasma mass spectrometry in plasma samples of 68 hemodialysis patients. The same elements (with exception of La and Mn) were also determined in whole blood after mineralization with high-purity nitric acid/hydrogen peroxide in a closed-pressurized microwave system. The accuracy and precision was checked by analyzing two Seronorm "whole blood" reference materials. All samples were con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 13 publications
7
47
0
Order By: Relevance
“…In an earlier study (Krachler et al, 1997a), we could establish 10-fold increased plasma Co concentrations in 68 hemodialysed patients (2.05 mgaL, range 1.14 to 3.25 mgaL) caused by clinical treatment. Probably, adults and infants do not have adequate mechanisms of homeostasis developed to prevent elevated serum Co levels.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In an earlier study (Krachler et al, 1997a), we could establish 10-fold increased plasma Co concentrations in 68 hemodialysed patients (2.05 mgaL, range 1.14 to 3.25 mgaL) caused by clinical treatment. Probably, adults and infants do not have adequate mechanisms of homeostasis developed to prevent elevated serum Co levels.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, whole blood, plasma, and serum are generally convenient samples for the determination of the trace element status of a person. A number of investigations have been carried out over the years to assess reference values for trace elements in these body liquids (Caroli et al, 1994;Krachler et al, 1997aand b, Ru Èkgauer et al, 1997. Almost all studies concentrated on the trace element status of adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Michael Krachler et al, who determined toxic and trace elements in the plasma samples of 68 haemodialysis patients by inductively coupled plasma mass spectrometry, had demonstrated a higher concentration of cadmium than the high limits for healthy adults [32]. D Van Renterghem et al, had demonstrated elevated concentrations of cadmium in the sera of five patients who were on haemodiafiltration [31].…”
Section: Resultsmentioning
confidence: 99%
“…Michael Krachler et al, had demonstrated a higher concentration of lead than the high limits for healthy adults [6]. Martegani et al, described a significant increase in the erythrocyte [7] protoporphyrin IX levels in patients with chronic renal failure and in those who were on haemodialysis.…”
Section: Discussionmentioning
confidence: 99%